PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PASAR PERUSAHAN YANG TERDAFTAR DI BEI - Mirdha Fahlevi SI (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2019)
This research analyzes the effect of dividend policy on market value of companies listed in Indonesia Stock Exchange. Multiple linear regression analysis is used to analyze the hypotheses. The hypothesis of this researh is based on three Ohlson equity valuation Models. The first model of hypothesis is based on permanent earning, the second model is based on expected future earnings and the third model is based on current earning. In the firt group of hypothesis, the impact of investment on company’s market value is 43,9% . In the second group of hypotheses the impact of investment on company’s market value is 38,9%. In the third group of hypotheses, the impact of investment on company’s market value is 43,1%. Based on theses data, the dividend policy is irrelevant in increasing the company's market value. But, the investment is relevant in increasing the comnpany’s market value. This research confrim Mondigliani and Miller dividend irrelevance theory in 1961